Dynamic modeling and applications in global economic analysis - Ianchovichina, Elena; Walmsley, Terrie Louise (Cambridge : Cambridge University Press, 2011)
A sequel to Global Trade Analysis: Modeling and Applications (Cambridge University Press, 1996, edited by Thomas W. Hertel), this new volume presents the technical aspects of the Global Trade Analysis Program's global dynamic framework (GDyn) and its applications within important global policy issues. The book covers a diverse set of topics including trade reform, growth, investment, technology, demographic change and the environment. Environmental issues are particularly well-suited for analysis with GDyn, and this volume covers its uses with climate change, resource use and technological progress in agriculture. Other applications presented in the book focus on integration issues such as rules governing foreign investment, e-commerce regulations, trade in services, harmonization of technical standards, sanitary and photo-sanitary regulations, streamlining of customs procedures, and demographic change and migration.
Theoretical structure of dynamic GTAP / Elena I. Ianchovichina and Robert A. McDougall -- Behavioral and entropy parameters in the dynamic GTAP model / Alla Golub and Robert A. McDougall -- An overview of the dynamic GTAP data base : the data base construction and aggregation programs / Robert A. McDougall [and others] -- A baseline scenario for the dynamic GTAP model / Terrie L. Walmsley, Betina V. Dimaranan, and Robert A. McDougall -- Welfare analysis in the dynamic GTAP model / Terrie L. Walmsley, Robert A. McDougall, and Elena I. Ianchovichina -- Implementing the dynamic GTAP model in the RunDynam software / Ken Itakura [and others] -- Assessing the impact of China's WTO accession on investment / Terrie L. Walmsley, Thomas W. Hertel, and Elena I. Ianchovichina -- Dynamic effects of the "new-age" free trade agreement between Japan and Singapore / Thomas W. Hertel, Terrie L. Walmsley, and Ken Itakura -- Resource use and technological progress in agriculture / Elena I. Ianchovichina, Roy Darwin, and Robin Shoemaker -- Global economic integration and land-use change / Alla Golub and Thomas W. Hertel -- The contribution of productivity linkages to the general equilibrium analysis of free trade agreements / Ken Takura, Thomas W. Hertel, and Jeffrey J. Reimer -- Global demographic change, labor force growth, and economic performance / Rod Tyers and Qun Shi -- Household saving behaviour in the dynamic GTAP model : evaluation and revision / Alla Golub and Robert A. McDougall -- Implications for global economic analysis / Elena I. Ianchovichina and Terrie L. Walmsley -- Appendix : Negative investment : incorporating a complementarity into the dynamic GTAP model / Terrie L. Walmsley and Robert A. McDougall -- Glossary of GDyn notation / Terrie L. Walmsley.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: International trade -- Mathematical models; International economic relations -- Mathematical models; International trade; International economic relations